Night Journeys - Avi; Nang Chan Yeema (United States of America Avon Books, Inc., 2000)
The year 1768. In eight years, the American Revolution will begin. Newly orphaned, Peter York has been adopted by a deeply religious Quaker farmer.
Keywords: Adult Fiction